2021
DOI: 10.4274/tao.2021.2021-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Topical Intranasal Fluorescein to Diagnose and Localize Cerebrospinal Fluid Leak: A Systematic Review

Abstract: Objective: This study evaluates the available evidence regarding using topical intranasal fluorescein (TINF) to diagnose and localize nasal cerebrospinal fluid (CSF) leak. Methods: A literature search was conducted through PubMed, the Cochrane Database, Scopus, and Ovid to identify the articles providing insight into using TINF to diagnose CSF leak preoperatively or to localize the leak intraoperatively. The articles from the database were screened and filtered by two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Different kinds of CSF leakage due to head injury, iatrogenic injury, and intracranial tumor, 33 , 34 , 35 , 36 as well as intrathecal invasion due to lumbar trauma, and spinal anesthesia, 37 are commonly seen in clinical practice. According to our results, both deep intrathecal invasion and CSF outflow can lead to elevated CSF AD biomarker levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different kinds of CSF leakage due to head injury, iatrogenic injury, and intracranial tumor, 33 , 34 , 35 , 36 as well as intrathecal invasion due to lumbar trauma, and spinal anesthesia, 37 are commonly seen in clinical practice. According to our results, both deep intrathecal invasion and CSF outflow can lead to elevated CSF AD biomarker levels.…”
Section: Discussionmentioning
confidence: 99%
“…No. KHB3481) and Amyloid-beta 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 (Thermo Fisher, Cat. No.…”
Section: Methodsunclassified
“…Fluorescein changes to a green color upon contact with CSF, and having the patient perform a Valsalva maneuver may lead to confirmation and localization 11 . A systematic review of seven studies found this to have a diagnostic accuracy rate of >96%, 12 though another systematic review astutely pointed out that only three studies before 2021 were utilized as pre‐operative diagnostic tools (as opposed to intraoperative), and all located already confirmed leaks 13 . Nevertheless, patients may not be actively leaking during the time of examination, which may be due to concurrent inflammation or a ball‐valve effect with intracranial contents during periods of low intracranial pressure 4,6,7 …”
Section: Current Methods In Diagnosismentioning
confidence: 99%